الرشوة وعلاقتها ببعض المتغيرات النفسية والشخصية : دراسة ميدانية في بعض السجون الجزائرية - شارف، جميلة; بقال، إسمى (جامعة الجنان - مركز البحث العلمي, 2018)
The current study sets up to investigate the psychological and social characteristics among the bribe taker in addition to examining its relationship to some psychological, social and behavioral variables. Accordingly, the researchers have administered a battery of standardized psychometric tests concerning self-concept, mental alienation and psychopathic deviance to a sample of 14 bribe takers among individual prisoners who were condemned for bribery crime in addition to a similar sample of individuals who were not concerned by bribery. Their range age varies from 25 and 65. The results of the study revealed that the bribe taker ischaracterized by a crude immature personality and that his concept of himself is distorted, aggressive or hostile towards the self and others, in addition to developing a sentiment of isolation, non-apathy and non-goal.
تسعى الدراسة الحالية للتعرف إلى الخصائص النفسية والاجتماعية لدى المرتشي، إضافة إلى معرفة هذه العلاقة ببعض المتغيرات النفسية والاجتماعية والسلوكية، وقد تكونت العينة من (14) مرتشياً من الأفراد المسجونين في السجون الجزائرية والمحكومين بجريمة الرشوة، إضافة إلى عينة مماثلة لها غير مرتشية، تراوحت أعمارهم بين (25 – 65) سنة، واستخدم لفحص العلاقة والتعرف على هذه السمات مجموعة من الأدوات قام الباحث بإعدادها وهي مقياس مفهوم الذات، مقياس الاغتراب النفسي، مقياس الانحراف السيكوباتي، أظهرت النتائج أن المرتشي يتسم بالشخصية الفجة وغير الناضجة اجتماعيا وانفعاليا واجتماعيا، وأن مفهومه عن ذاته مشوه أو محرف، كما يتسم بالعدوانية أو العدائية نحو الذات والآخرين، إضافة إلى شعوره بالعزلة والعجز واللامعيارية واللاهدفية.
Keywords: الانحراف السيكوباتي; مفهوم الذات; سمات الشخصية; الرشوة; الاغتراب النفسي